PENERAPAN PROTOKOL KESEHATAN BERBASIS CHSE PADA DEPARTEMEN HOUSEKEEPING DI SUDAMALA SUITES & VILLAS SENGGIGI LOMBOK - Rekta Deskarina; Baiq Uswatun Hasanah (Sekolah Tinggi Pariwisata Ambarrukmo Yogyakarta, 2022)
The spread of covid-19 has destroyed the tourism sector, especially hotel industry. To rebuilt the economic wheels as usally, the scenario of new normal is applied. In tourism sector by the ministry of tourism and economy creative has launched protocol namely CHSE (Cleanliness, Health, Safety, dan Environment Sustainability) to give guest guarantee about cleanliness, heatth and safety. This research has purpose to know implimentation of CHSE in housekeeping department with qualitative as metode. Data collection as carried out by observation, interviews and documentation. The result of research is implimenation of chse into indicator are cleanliness, health, and Environment Sustainability applied regarding to guiding book by Kemenparekraf and in the good category.Keywords: Hotel, Housekeeping Department, Covid-19, CHSE